Effect of Partial Shrouds on the Performance and Flow Field of a Low-Aspect-Ratio Axial-Flow Fan Rotor - N. Sitaram; G. Ch. V. Sivakumar (International Journal of Rotating Machinery)
The flow field at the rotor exit of a low aspect ratio axial flow fan for different tip geometries and for different flow coefficients is measured in the present study. The following configurations are tested: (1) rotor without partial shroud, designated as rotor (wos), (2) rotor with partial shroud, designated as rotor (ws), and (3) rotor with perforated (perforations in the shape of discrete circular holes) partial shroud, designated as rotor (wps). From steady state measurements, the performance of rotor (wps) is found to be the best. Both the rotors with partial shrouds have stalled at a higher flow coefficient compared to that of rotor (wos). From periodic flow measurements, it is concluded that the low velocity region near the tip section is considerably reduced with the use of partial shrouds with perforations. The extent of this low velocity region for both rotor (wos) and rotor (wps) increases with decreasing flow coefficient due to increased stage loading. This core of low momentum fluid has moved inwards of the annulus and towards the pressure side as the flow coefficient decreases. The extent of the low momentum fluid is smaller for rotor (wps) than that of rotor (wos) at all flow coefficients.